136k views
1 vote
Express in simplest form : cubed root of a^6b^9/-64. Show work

User Dessus
by
7.8k points

1 Answer

2 votes
The answer is
( a^(2) b^(3) )/(-4)


\sqrt[3]{ ( a^(6) b^(9) )/(-64) } = \frac{ \sqrt[3]{a^(6) b^(9)} }{ \sqrt[3]{-64} } = \frac{ \sqrt[3]{a^(6)} * \sqrt[3]{ b^(9)} }{ \sqrt[3]{-64}}
Since (xᵃ)ᵇ = xᵃ*ᵇ, then:
a⁶ = (a²)³
b⁹ = (b³)³
Also: 64 = 4³

\frac{ \sqrt[3]{a^(6)} * \sqrt[3]{ b^(9)} }{ \sqrt[3]{-64}}= \frac{ \sqrt[3]{( a^(2))^(3) }*\sqrt[3]{( b^(3))^(3) } }{\sqrt[3]{( -4)^(3) }} = ( a^(2) * b^(3) )/(-4)
User Mostar
by
7.7k points